Improving Tiger Sprong Learning Outcomes Through the Homogeneity Psycho-Cognition Strategy in Grade XI-2 Students of SMA Negeri 3 Ambon - Simon Stewar Luarmasse; Albertus Fenanlampir; Johanna Matitaputty (Peneliti.net, 2026)
This study aimed to describe and analyze the improvement of tiger leap (loncat harimau) learning outcomes through the application of the Homogeneity Psycho-Cognition strategy among class XI-2 students of SMA Negeri 3 Ambon. The research employed the Classroom Action Research (CAR) method using the Kemmis and McTaggart spiral model, which consists of four stages: planning, acting, observing, and reflecting, and was conducted over two cycles. The subjects comprised 30 students of class XI-2. The instruments were a teaching module and a performance assessment, while the data were analyzed quantitatively through the average score and the percentage of classical learning completeness. The results revealed a significant improvement. In cycle I, classical completeness reached only 47% (14 students) with a class average of 74, whereas in cycle II completeness increased to 100% (30 students) with an average of 80. The disparity in learning outcomes also decreased, indicated by a narrowing of the score range from 49 to 19 points. The main obstacle in cycle I, namely the gap between cognitive mastery and psychomotor ability, particularly among female students, was overcome through safety reassurance, increased motivation, and targeted feedback. It is concluded that the Homogeneity Psycho-Cognition strategy effectively improves tiger leap learning outcomes.